Free radical scavenging activity of Syzygium polyanthum leaves - Yassir, M. A.; Abdul Kadir, Arifah; Ismail, Amin; Othman, Fauziah (2012)
There is a growing interest in the usage of antioxidants in attempt to prevent oxidative damage caused by free radicals in the human body. This study was undertaken to determine the free radical scavenging activity of methanolic extract of Syzygium polyanthum (SP) leaves against the stable 2,2-Azino-bis-3-ethylbenzothiazoline-6-sulfonic Acid (ABTS) radical by using an ELISA reader technique. The results showed that SP directly reacted and quenched ABTS free radicals in the system. The IC50 value of SP was significantly (P <0.05) more effective than that of ascorbic acid, and quenched significantly (P <0.05) more ABTS radicals at low concentrations (5 and 10 μg/mL) than that of ascorbic acid. Moreover, the total antioxidant capacity (TAC) of SP was also significantly (P <0.05) higher than that of ascorbic acid under same experimental condition. In conclusion, the results of ABTS assay reveal potent antioxidant and free radical scavenging activity of SP higher than that of standard ascorbic acid which may serve as a new natural antioxidant.